2018
DOI: 10.3390/ijerph16010069
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Quality of Life and Health Services Utilization among Elderly People in Rural Vietnam

Abstract: As in much of the world, the elderly population in Vietnam is growing rapidly with two-thirds of them currently living in rural areas. Besides limited access to quality healthcare services, they also have unique health profiles and needs due to various factors, including the highly skewed sex ratio of more women residing in rural areas. However, the relationship between gender, health-seeking behaviors, and health outcomes in this under-served population has not been well characterized. This study sought to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 16 publications
6
38
3
1
Order By: Relevance
“…This was consistent with previous studies in Vietnam [66][67][68]. Furthermore, men had a better HRQoL score than women did, which was found in the current study and in previous studies [68,69]. People with comorbidities had a lower HRQoL score than those people without, which was in the line with previous studies [68,70,71].…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with previous studies in Vietnam [66][67][68]. Furthermore, men had a better HRQoL score than women did, which was found in the current study and in previous studies [68,69]. People with comorbidities had a lower HRQoL score than those people without, which was in the line with previous studies [68,70,71].…”
Section: Discussionsupporting
confidence: 93%
“…This study found that the differences in EQ‐5D indexes or EQ‐VAS scores between men and women were not statistically significant, whereas a recent study of elderly people in rural Vietnam found better health outcomes for men than women . One possible reason for this disparity is that the subjects in the present study were elderly living in the city.…”
Section: Discussioncontrasting
confidence: 81%
“…One possible reason for this disparity is that the subjects in the present study were elderly living in the city. In addition, Vietnam has a skewed sex ratio in the elderly age group due in part to war‐related deaths among men, resulting in more elderly women than men living without a spouse or partner . Furthermore, fewer women than men in rural Vietnam had support from a caregiver, spouse or children .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public Health 2020, 17, 1966 2 of 14 This last aspect is primarily related to the social construction of reality that often offers a stereotyped representation of "rural women" [13]. Moreover, it is important to take into account that their occupational integration in these areas is more complex [14], which doubtless affects their well-being and quality of life [15]. In light of this, it should be borne in mind that subjective well-being and satisfaction with life are closely associated with mental health [16].…”
Section: Introductionmentioning
confidence: 99%